PENGARUH MODEL PEMBELAJARAN CO-OP CO-OP TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS VIII - Fitriana Rahmawati (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2021)
This study aims to determine the effect of the Co-Op Co-Op learning model on students' mathematical communication skills. This research is a quantitative research with an experimental method and uses a Pre-Experimental design in the form of a Posttest-Only Control Design. The population in this study were all class VIII SMP Perintis 1 Bandar Lampung which consisted of 77 students. Samples were taken by simple random sampling technique. The sample consisted of two classes, namely class VIII.1 as the experimental class with 27 students and class VIII.2 as the control class with 25 students. Based on hypothesis testing, it is obtained that students' mathematical communication skills with the Co-Op Co-Op model are higher than conventional learning. From the results of research and data analysis, it can be concluded that learning begins with a question learning model that has a positive effect on mathematical communication skills of class VIII students in odd semesters. Pioneer 1 Junior High School Bandar Lampung for the academic year 2021.